Comparative Analysis of Immunization and Immunization Coverage in Children of Russian Federation Federal Districts - Polina R. Grinchik; Leyla S. Namazova-Baranova; Marina V. Fedoseenko; Asiya A. Girina; Sergey V. Kovalev; Anastasia V. Mazokha; Elena D. Makushina; Elena I. Malinina; Anastasia Yu. Musikhina; Olga A. Perminova; Nina Y. Plenskovskaya; Tatiana E. Privalova; et al. (Педиатрическая фармакология, 2022)
Background. One of the effective ways to maintain the epidemic well-being of vaccine preventable diseases is to estimate immunization rates and coverage.Objective. The aim of the study is to conduct comparative analysis of immunization levels among children in various regions of Russian Federation. Methods. Children aged from 6 months to 15 years conducted comparative analysis of indicators of documented immunization and immunization coverage according to forms 112/y and 036/y in four federal districts of Russian Federation. The immunization rate was estimated in individuals who had completed vaccination scheme according to the national immunization schedule (NIS) (of 2014). Immunization coverage was estimated by number of persons with at least one vaccination in past medical history.Results. The analysis was performed on 2687 children medical records from the Central, Ural, Siberian and Volga federal districts (FD). BCG immunization rates in all FDs tend to be 100%. There are high levels of immunization against hepatitis B, as well as against measles, rubella and parotitis (the lowest values are noted in the Central Federal District: against hepatitis B — 74%, against measles, rubella, mumps — 69%, high — in the Volga Federal District: against hepatitis B — 95%, against measles, rubella, mumps — 97%). There is significant mismatch in immunization rates and immunization coverage for pertussis, diphtheria, tetanus and poliomyelitis in all FDs (from 20% to 40%) indicating that there are disturbances in vaccination schemes. Low immunization rates are noted against pneumococcal infection (from 12% in the Siberian Federal District to 36% in the Volga Federal District) and influenza (from 0.5% in the Volga Federal District to 9% in the Ural Federal District).Conclusion. The highest immunization rates for all infections included in the NIS (apart from influenza) were revealed in the Volga Federal District. Influenza immunization rate is critically low in all FDs.